The determinant factors that influence the generations Z and older generations in Malaysia toward cashless society - M. T., Hirnissa; Mohd Ashhari, Zariyawati; R., Fadilla (Global Academic Excellence, 2021)
This study highlights the key predictors that influence Malaysia’s cashless society rate. Unified Theory of Acceptance and Usage of Technology (UTAUT) was adopted in this research, and main constructs such as speed of transaction, personal security, convenience and safer, social influences, perceived usefulness, compatibility, business readiness, and financial costs. The sample size for this study is 357 Malaysian aged 18 years old and above. There are two generations under 25 years old and below categorized as Generations Z, while age 25 years old and above are categorized as Older Generations. Primary data had been used and collected through an online questionnaire method. Using SPSS software, regression analysis results showed that four of the independent variables had a significant relationship with the dependent variables. The speed of transaction, convenience and safer, perceived usefulness, and compatibility did influence Malaysian towards cashless society adoption.